CHALLENGES AFFECTING THE COMMERCIALIZATION OF INTELLECTUAL PROPERTY RIGHTS IN THE GAMBIA’S TEXTILE INDUSTRY - Ceesay, Muhamed Lamin (Faculty of Law, Universitas Lampung, 2024)
There has been significant deterioration in the textile industry of The Gambia over the years which has resulted to loss of jobs, minimal revenue and preference for foreign goods over locally made. As a result, this study examines the challenges affecting the use of intellectual property rights in the textile industry of The Gambia to maximize the quality and efficiency of their goods and service. Participants were selected through a purposive sampling, and data for this research was collected through focus group discussion with producers, retailers and users of textile; unstructured interviews with three heads of institutions; and an observational study with producers. The data was analysed using the thematic analysis. The findings of the research reveal that the main challenges encountered by the textile industry regarding the use of intellectual property rights in their businesses is due to lack of awareness since most producers, and retailers have never heard of intellectual property rights nor obtained any trainings on it. Also, lack of enforcement against unlawful copying of textiles by infringers has been a great discouragement for many producers and retailers in the textile industry of The Gambia not to acquire intellectual property rights. Furthermore, lack of financial support from the government has affected the growth and productivity of the textile industry of The Gambia. Therefore, the textile industry of The Gambia should receive constant awareness trainings from intellectual property rights which will encourage them to appreciate, register and use their intellectual property rights over the creative works. The Gambian government should also provide the required facilities to police and border control agencies to enforce against unlawful copies of locally made textiles and other sorts of infringements. Equally, The Gambian government should provide enough financial support and award grants to the textile industry.